Comparative analysis of selected business indicators of state forest companies : Komparativna analiza odabranih pokazatelja poslovanja državnih šumarskih poduzeća - Posavec, Stjepan, inženjer šumarstva (Array, 2021)
A company that handles natural resources such as forests is a complex economic entity. In addition to economic performance at annual level, the biological component of sustainable forest management should also be considered. It is therefore extremely important to achieve efficient business performance. Financial analysis is a process of determining important business and financial characteristics of a company from accounting data. It is characterized by a wide use of financial reports and various financial indicators - key figures. The paper presents business indicators of the main state-owned forest companies in selected countries of South East Europe (Croatia, Slovenia, Serbia, Bosnia and Herzegovina, and North Macedonia) using the method of comparative analysis based on financial reports (such as balance sheet and income statement). In countries where there are more than one state-owned forest companies, they were selected according to their importance for forest management and business results (share of forests, number of employees, profit and annual felling). The research results show the revenue and expenditure of the selected companies and profitability indicators such as return on equity (ROE) and return on assets (ROA). According to the annual business reports for 2017 and 2018, the company Croatian Forests Ltd. has the highest number of employees (7787 in 2018). The highest ratio ROA (32.17) and ROE (39.82) were achieved in the Slovenian state forestry company in 2017, which was founded in 2016. For 2018, the best results are achieved in the Slovenian Forest Company (SiDG), while the weakest results are achieved in the State Forest Company in North Macedonia. The profit per employee decreased in 2018 for most companies, but most significantly in North Macedonia, where it was four times lower.